Implementasi Konsep âPretensious Momentâ Tradisional Lombok Pada Perancangan Interior Lobby Dan Area Komersil âThe Lomboâ Hotel Resort Di Lombok - Andriani, Evelyna (Intra, 2015)
Lobby interior design and commercial areas THE Lombo Hotel Resort in Lombok is a commercial facility design projects that can provide value relaxation, recreational, aesthetic, the resort users, the design continues to raise the value of the locality (such as indigenous culture, handicrafts, and decorative elements) Lombok , and may help the effectiveness and efficiency of operational systems service resort. Lobby interior design and the commercial area of this resort hotel will reflect the cultural hallmark of Lombok Island. Besides being able to enjoy the natural charms, visitors also can indirectly owned recognize culture Lombok island itself. Lobby interior design and commercial areas this resort hotel carries the brand image of THE Lombo Hotels & Resorts who became the first 5 star resort hotel on the island of Lombok. The expected impact of this design is that it can increase the value of tourism in Lombok Island and can promote Lombok Island.